PENGARUH LINGKUNGAN KERJA DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Kasus UKM Alkijo Laundry Yogyakarta) - Agus Dwi Cahya; Lukito Oki H; Sandy Khristian; Shinta Noriyah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study was to determine the effect of the Work Environment and Compensation on UKM Alkijo Laundry in Sleman Regency, Yogyakarta. This type of research is descriptive research using a quantitative approach. The research subjects are employees of Alkijo Laundry. Primary data was obtained from a questionnaire with 15 respondents with saturated samples. Data were analyzed using multiple linear analysis. The results of the research on the T test indicate that the Work Environment Variable (X1) has a positive and significant effect on employee performance (Y) with a value of 0.002 and the Compensation variable (X2) has no significant effect on employee performance (Y) with a value of 0.082. In the results of the F test the work environment and compensation simultaneously on the performance of the appointed employee with a significance value of 0.006